2008
DOI: 10.1159/000164393
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory Cytokine Profiles of Patients with Elderly-Onset Rheumatoid Arthritis: A Comparison with Younger-Onset Disease

Abstract: Background: Little is known about the differences in the immunopathogenesis between elderly-onset rheumatoid arthritis (EORA) and younger-onset RA (YORA) and the factors responsible for their clinical characteristics. Objective: It was the aim of this study to investigate proinflammatory cytokines of EORA patients and compare them with those of YORA patients. Methods: Serum levels of interleukin (IL)-1β, IL-6, IL-8, tumor necrosis factor (TNF)-α and interferon (IFN)-γ were determined by cytometric bead array i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(63 citation statements)
references
References 83 publications
6
49
0
8
Order By: Relevance
“…Consistent with our findings (Fig. 1G), it has been reported that IL-1␤ is elevated in serum during RA, and this is correlated with higher disease activity (27). However, the signaling network of IL-1␤ in RAFLS is still poorly understood.…”
Section: Resultssupporting
confidence: 92%
“…Consistent with our findings (Fig. 1G), it has been reported that IL-1␤ is elevated in serum during RA, and this is correlated with higher disease activity (27). However, the signaling network of IL-1␤ in RAFLS is still poorly understood.…”
Section: Resultssupporting
confidence: 92%
“…Although side effects can be detrimental to the physical and psychological functioning of all cancer survivors, older cancer survivors, due to additional age-related declines, may have more difficulty recovering from treatment-related side effects [3]. In addition, aging in the absence of a cancer history is associated with a decline in physical and psychological function, including sarcopenia, reduced strength, 5 reduced bone mineral density [6], lower functional capacity [7–8], arthralgias [9], depressive symptoms [10], anxiety [11], and cognitive difficulties [12]. Cancer and its treatments can exacerbate these common decrements in function and lead to additional impairments [3, 1314].…”
Section: Introductionmentioning
confidence: 99%
“…In EORA, IL-6 levels are higher and TNF levels lower than in young subjects. Furthermore, in both age groups, a positive correlation has been found between IL-1, IL-6, TNF, IFN-␥ (Interferon), IL-8 and the DAS28 score, and between IL-1 and TNF and joint erosions [17]. In the elderly population, high levels of IL1ra and TNF were generally associated with an increased risk of death at one year [18].…”
Section: Effective Treatmentsmentioning
confidence: 96%